Purchase Intention of Healthy Foods: The Determinant Role of Brand Image in the Market of a Developing Country - Gallardo-Canales, R; Escobar-Farfan, M (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In the current consumer context, the trend towards a healthy lifestyle has significantly increased the demand for healthy foods. This study aims to identify the relationship between the brand image (BI) and purchase intention (PI) of these products and how variables such as perceived brand quality (BPQ) and brand satisfaction (BS) influence brand trust (BT) and brand loyalty (BL) in this relationship. The methodology includes a quantitative approach, using non-probability convenience sampling. Using an online survey, data were collected from 637 consumers. Analyses were performed using structural equation modeling (SEM-PLS). The results show no significant correlation between BI and PI, but BI significantly impacts BPQ, BS, BT, and BL. Furthermore, BPQ positively influences BS, BT, and BL, but it does not have a direct influence on PI. The findings suggest that a positive brand image satisfies consumers and generates long-term trust and loyalty. However, perceived quality does not always translate into purchase intention due to various barriers. Practical implications highlight the importance of building a strong and positive brand image to encourage demand for healthy products. © 2024 by the authors.